2019
DOI: 10.1186/s12711-018-0444-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide associations and detection of potential candidate genes for direct genetic and maternal genetic effects influencing dairy cattle body weight at different ages

Abstract: BackgroundBody weight (BW) at different ages are of increasing importance in dairy cattle breeding schemes, because of their strong correlation with energy efficiency traits, and their impact on cow health, longevity and farm economy. In total, 15,921 dairy cattle from 56 large-scale test-herds with BW records were genotyped for 45,613 single nucleotide polymorphisms (SNPs). This dataset was used for genome-wide association studies (GWAS), in order to localize potential candidate genes for direct and maternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 52 publications
1
29
0
Order By: Relevance
“…Strong evidence of genomic signaling from chromosome 5 at the vicinity of base pair 106,987,567 was found by TPM at windows size of 2 [-log(P)=6.48e -10 ]. This finding is consistent with those of other studies that reported a weight gain gene CCND2 at the same genomic location [2,21,33]. Estimation of the proportion of genetic variance explained by detected SNPs found to be around 13% based on the Bayesian model.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Strong evidence of genomic signaling from chromosome 5 at the vicinity of base pair 106,987,567 was found by TPM at windows size of 2 [-log(P)=6.48e -10 ]. This finding is consistent with those of other studies that reported a weight gain gene CCND2 at the same genomic location [2,21,33]. Estimation of the proportion of genetic variance explained by detected SNPs found to be around 13% based on the Bayesian model.…”
Section: Discussionsupporting
confidence: 92%
“…To determine whether the various assumptions regarding genetic structure of the body weight gave different results, the number of mixtures were increased. BayesR [29] assumed a mixture of four normal distributions for predictions of SNP effects (assumed to be 0.00001, 0.0001, 0.001, and 0.01 genetic variances) in model (2). For each phenotype, the Markov Chain Monte Carlo (MCMC) algorithm was run for 1.000.000 samples, and the first 2000 samples were discarded as burn in period.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have reported QTLs and genes associated with growth traits in cattle (e.g., body weight and average daily gain) using the GWAS strategy [40,41]. However, few QTLs have consistently been identified as being associated with growth traits among breeds of cattle, including for Brangus heifers [42], Japanese Black (Wagyu) cattle [43], Charolais beef cattle [8], Siberia cattle [1], Nellore cattle [3], and the Chinese Simmental beef cattle examined in this study.…”
Section: Potential Genomic Regions and Candidate Genes Reveal The Commentioning
confidence: 85%